Proper Names Translation in “The Secret Garden” Novel by Frances Hodgson Burnett - Raditya, I Made Deva; Agung, I Gusti Ayu Mahatma (Universitas Cokroaminoto Palopo, 2023)
In literary works such as novels, language plays a vital role in telling stories. Novels that will be distributed to readers from various countries will usually be translated first, and it is the job of the translator to maintain several important elements such as proper names so that they remain under the original meaning of the text. This way, readers can fully grasp the essence of the story in the translated version. The main aim of this study is to discover the different kinds of proper names and translation techniques used in Frances Hodgson Burnett's novel, The Secret Garden. To achieve this, the research incorporates Newmark's theory. The data was collected through observation and documentation, with notes being taken during the process. As a result, the study identified three distinct types of proper names in The Secret Garden novel, such as people’s names, geographical terms, and names of objects. Furthermore, during the research, seven different translation procedures were discovered. These procedures include transference, naturalization, couplets, expansion, shift or transposition, cultural equivalent, and literal translation. Out of all the translation procedures studied, the transference procedure was the one most used. It allowed the translator to retain the original names as much as possible while translating the novel into another language.